Inherited Thrombotic Thrombocytopenic Purpura in Children - Hassenpflug, Wolf Achim; Budde, Ulrich; Schneppenheim, Sonja; Schneppenheim, Reinhard (Seminars in Thrombosis and Hemostasis, 2014)
Congenital thrombotic thrombocytopenic purpura (TTP) or Upshaw–Schulman syndrome is caused by homozygous or compound heterozygous mutations in the ADAMTS-13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) gene. We investigated 30 patients with congenital TTP and analyzed clinical data and underlying ADAMTS-13 mutations. All patients showed virtually no ADAMTS-13 activity in plasma. Individual disease burden ranged from mild courses with rare episodes of mild thrombocytopenia to severe courses with chronic kidney disease and central nervous system (CNS) lesions. Two patients died due to complications of TTP. If initiated in a timely manner, plasma transfusions offer a reliable treatment to prevent organ damage. We identified 30 different causative mutations in the ADAMTS-13 gene. Our data do not support the idea of a tight correlation between ADAMTS-13 genotype and severity of disease. The type and magnitude of exogenous triggers for acute bouts of TTP as well as endogenous individual factors participating in the inflammatory response likely represent the foremost determinants of individual clinical courses. Future developments should aim at improving early diagnosis of TTP. To improve feasibility of prophylaxis and treatment of congenital TTP, recombinant ADAMTS-13 therapeutics are highly anticipated.
Keywords: ADAMTS-13; Upshaw–Schulman syndrome; thrombotic thrombocytopenic purpura; von Willebrand factor; molecular genetics